Does Yik Yak Promote Risky Health Behavior on College Campuses?. Issue 4 (3rd April 2018) - Wombacher, Kevin; Reno, Jenna E.; Williams, Gregory A.; Johnson, Lauren
ABSTRACT: This study offers an analysis of how healthy and risky behaviors are discussed on an emerging social media platform. We sought to understand what behaviors are communicated and if they are encouraged or discouraged. We completed a content analysis of messages ( n = 3, 776) posted to Yik Yak captured three times a day on 4 days of the week across two separate weeks. We analyzed messages to determine the category of the behavior, an appraisal of the behavior, and normative voting feedback. Our results show that risky behaviors were discussed with greater frequency and received more user votes than healthy behaviors. Exposure to these messages could influence other students' perceptions of norms associated with these risky behaviors. We suggest further research to determine how Yik Yak may affect normative perceptions on college campuses.